Red cell alloimmunization in transfusion-dependent and transfusion-independent beta thalassemia: A review from the Eastern Mediterranean Region (EMRO). (December 2019) - Al-Riyami, Arwa Z.; Daar, Shahina
Abstract: Background: β-Thalassemia is considered one of the common hemoglobin disorders in the Arabian Peninsula. Red blood cell (RBC) transfusion is a crucial component of the management of transfusion-dependent β-Thalassemia patients. Patients with Thalassemia Intermedia (TI), also known as non-transfusion dependent β-thalassemia, have a wide clinical presentation and variable transfusion dependence. Rates of RBC alloimmunization and its risk factors in transfusion-dependent β-thalassemia patients varied between different reports. Risk of alloimmunization is higher in TI patients. Material and methods: A literature review on existing reports on alloimmunization rates and risk factors in transfusion dependent and non-transfusion dependent β-thalassemia in the Eastern Mediterranean region was performed. Results: A total of 17 publications were found. Reported rates of alloimmunization among transfusion-dependent β-Thalassemia patients ranged between 2.87 and 30 % and between 6.8 and 19.5 % among TI patients. Most centers utilize ABO and RhD matched RBCs. The most common antibodies described are anti-K and anti-E. The risk factors described included age at onset of transfusion, gender, history of splenectomy, duration of transfusion and number of units transfused. Rate of autoantibody formation ranged between 0.1 and 45 %. Conclusion: Our review showed variable alloimmunization rates and risk factors in thalassemia patients and scant data on TI patients. The commonest antibodies are anti-K and anti-E. Further studies are required in addressing the rate of alloimmunization, cross-match requirements and role of genotyping in this group of patients. Transfusion support of patients with thalassemia necessitates the availability of blood bank facilities and specialized expertise.